A Comment on Safe Assets by Barro et al. (2022) - Guillaume Coqueret; Maria Elena Filippin; Martial Laguerre; Christoph Weber (Institute for Replication (I4R), 2024)
Barro et al. (2022) investigate the quantity of safe assets held in the cross-section of developed countries and find that the average safe-asset ratio (ratio of safe assets to total assets) was 37% in 2015 and has remained relatively stable over time. They also document a crowding-out coefficient for private bonds relative to public bonds of around -0.5. In the second part of the analysis, they simulate a heterogeneous agent model with rare disasters and risk aversion to match the empirical findings. This report seeks to reproduce and confirm their results. Overall, we were largely able to replicate their findings and propose a few robustness checks. Apart from two regression outputs for which the signs and significance do not change, our results are very close to those of the original paper. Alternative models and estimators do not change the signs or significance levels. A more systematic approach to the parameter values in the simulations also points towards solid conclusions.
Keywords: E44; E51; G11; G12; G51; 330; Replication; reproducibility; robustness